Efeitos do treinamento físico aeróbio nas alterações pulmonares induzida por diferentes produtos da poluição atmosférica - Rennó, Adriano Silva (2016)
Air pollution is a growing problem worldwide, inducing and exacerbating several diseases. Among the several components of air pollutants, particulate matters (PM), especially thick (10-2,5µm; PM 10) and thin (≤2,5 µm; PM 2.5), are breathable particles that easily can be deposited into the lungs, resulting in lung and systemic inflammation. Although physical activity is strongly recommended, its effects when practiced in polluted environments are questionable. Therefore, the present study evaluated the pulmonary and systemic response of concomitant treadmill training with PM 2.5 and PM 10 exposure. Treadmill training inhibited PM 2.5 and PM 10induced accumulation of total leukocytes (p<0.001), neutrophils (p<0.001), macrophages (p<0.001) and lymphocytes (p<0.001) in bronchoalveolar lavage (BAL), as well as the BAL levels of IL-1beta (p<0.001), CXCL1/KC (p<0.001) and TNF-alpha (p<0.001), while increased IL-10 levels (p<0.05). Similar effects were observed on accumulation of polymorphonuclear (p<0.001) and mononuclear (p<0.01) cells in the lung parenchyma and also in the peribronchial space. Treadmill training also inhibited PM 2.5 and PM 10-induced systemic inflammation, as observed in the number of total leukocytes (p<0.001), and in the plasma levels of IL1beta (p<0.001), CXCL1/KC (p<0.001) and TNF-alpha (p<0.001), while increased IL10 levels (p<0.001). Aerobic treadmill training performed concomitantly to particulate matter exposure, inhibits pulmonary and systemic inflammation induced by exposition to such particles.